The Effect of Heat Shock on Anopheles Arabiensis Patton (Diptera: Culicidae) Larvae - Muna Abd Al-Wahed Banian (Journal of Global Pharma Technology, 2019)
The objective of this study was to examine the effect of heat shock on Anopheles arabiensis larvae and for controlling mosquitoes. Samples of larvae were collected from Iraq. The larvae were exposed to various temperatures 30, 35, 40, 45 and 50°C for 10 minutes (as heat shock period). Larval mortality was recorded. The data was analyzed to calculate the quantity of heat (kj) that was added, the corrected mortality, the regression line and the correlation coefficient. It was found that heat shock of 30°C has no effect on larvae, but heat shock of 35, 40, 45 and 50°C produced mortality, while heat shock of 30 and 35°C has no effect on some aquatic organisms. The heat shock of 40.6°C and 48.94°C produced mortality in 50% and 95% of larval populations, respectively. The study showed that the heat shock of 40°C can be used to control the aquatic stages (Larvae) of mosquito (Anopheles arabiensis). The results of this work could be further tested in small pools, man- wholes of the bath rooms small containers used to keep drinking water and water pot, “zeer”